Compensatory upregulation of PD-1, LAG-3, and CTLA-4 limits the efficacy of single-agent checkpoint blockade in metastatic ovarian cancer - Huang, Ruea-Yea (Oncoimmunology, 2016)
Tumor-associated or -infiltrating lymphocytes (TALs or TILs) co-express multiple immune inhibitory receptors that contribute to immune suppression in the ovarian tumor microenvironment (TME). Dual blockade of PD-1 along with LAG-3 or CTLA-4 has been shown to synergistically enhance T-cell effector function, resulting in a delay in murine ovarian tumor growth. However, the mechanisms underlying this synergy and the relative contribution of other inhibitory receptors to immune suppression in the ovarian TME are unknown. Here, we report that multiple immune checkpoints are expressed in TALs and TILs isolated from ovarian tumor-bearing mice. Importantly, blockade of PD-1, LAG-3, or CTLA-4 alone using genetic ablation or blocking antibodies conferred a compensatory upregulation of the other checkpoint pathways, potentiating their capacity for local T-cell suppression that, in turn, could be overcome through combinatorial blockade strategies. Whereas single-agent blockade led to tumor outgrowth in all animals, dual antibody blockade against PD-1/CTLA-4 or triple blockade against PD-1/LAG-3/CTLA-4 resulted in tumor-free survival in 20% of treated mice. In contrast, dual blockade of LAG-3 and CTLA-4 pathways using PD-1 knockout mice led to tumor-free survival in 40% of treated mice, suggesting a hierarchical ordering of checkpoint function. Durable antitumor immunity was most strongly associated with increased numbers of CD8(+) T cells, the frequency of cytokine-producing effector T cells, reduced frequency of Tregs and arginine-expressing monocytic myeloid-derived suppressor cells in the peritoneal TME. These data provide a basis for combinatorial checkpoint blockade in clinical intervention for ovarian cancer.